The theology of sustainability practice: How cities create hope - Newman, Peter (2018)
© Springer International Publishing AG, part of Springer Nature 2018. All rights reserved. Reflecting on a lifetime of sustainability practice as an academic, politician, public servant, and community activist, I have drawn on how theology has provided the roots of engagement in tackling the issues of change. Understanding the role of cities in theological history enables us to see how the global and local, the personal and the political, are linked in the journey we need to take towards sustainability. Key themes will be how nature and cities are intertwined, the role of prophets, the competing visions of a future city that have guided urban planners for centuries, and the role of activism and good work as a source of hope in creating the city of the future.